The effects of electronic games on the behaviors of students in elementary stages، their social states and their academic achievements - Al-Shihri, Abdul Rahman Saad (Journal of Educational and Psychological Sciences, 2019)
The most interesting in electronic games by children let psychologists and experts to study these games and their impact on their users from different perspectives. It has two sides of effects. They have positive aspects that appear in many aspects of the child’s life. Besides the education that the child acquires through increasing the concepts، information and skills development، they develop intelligence and speed of thinking. Many games contain puzzles and need mental skills to solve them. On the planning and initiative، and saturation of the imagination of the child in an unprecedented manner، and increase its activity and vitality، and become a high knowledge of modern technology، and good to deal with and use and dedicated to his benefit. It also encourages children to devise creative solutions to adapt to and adapt to the conditions of the game، and extend their impact to the practical reality; it enables him to apply some of the skills he gained through playing on the ground in real life. But on the personal level it develops the child’s violence and the sense of crime because the large proportion of these games depends on the child’s amusement and enjoyment of killing others، and teach adolescents methods and methods of committing the crime and tricks، As they develop in their minds violence and aggression through the frequent exercise of such games، the result is a violent and aggressive child. These games also make the child live in isolation from others، and the ultimate goal is to satisfy his desires to play. Thus، the child’s self-centered personality، self-love and introversion are formed and affected the communities that are widespread. The rate of murder and theft has increased As well as moral crimes، and these games have also been shown to affect the general health of the child in the long term; it leads to the injury of many health diseases and mental disorders، and playing for long periods of the child has the behavior of alcoholism Aloswasi.